2015
DOI: 10.2147/ceor.s86369
|View full text |Cite
|
Sign up to set email alerts
|

Health and economic outcomes associated with uncontrolled surgical bleeding: a retrospective analysis of the Premier Perspectives Database

Abstract: BackgroundBleeding remains a common occurrence in surgery. Data describing the burden of difficult-to-control bleeding and topical absorbable hemostat use are sparse. This study was conducted to estimate the clinical and economic impact that remains associated with uncontrolled surgical bleeding, even when hemostats are used during surgery.MethodsThis US retrospective analysis used the Premier Perspectives Database. Hospital discharges from 2012 were used to identify patients treated with hemostats during eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Bleeding is a frequent complication of surgery that can lead to substantial morbidity and mortality, longer surgeries and hospital stays, and increased total hospital costs [ 1 5 ]. Use of meticulous intraoperative hemostasis to reduce the risk of bleeding complications can be expected to have tremendous clinical and economic benefits [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding is a frequent complication of surgery that can lead to substantial morbidity and mortality, longer surgeries and hospital stays, and increased total hospital costs [ 1 5 ]. Use of meticulous intraoperative hemostasis to reduce the risk of bleeding complications can be expected to have tremendous clinical and economic benefits [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding is a frequent complication of surgery that can lead to substantial morbidity and mortality, longer surgeries and hospital stays, and increased total hospital costs [ 1 5 ]. Use of meticulous intraoperative hemostasis to reduce the risk of bleeding complications can be expected to have tremendous clinical and economic benefits [ 1 , 3 ]. In addition to conventional surgical methods (i.e., suturing and electrocautery), absorbable topical hemostatic agents can be used to improve surgical hemostasis [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 4 , 9 , 13 16 A large, US premier database study demonstrated that all-cause costs were significantly higher in patients with uncontrolled ($24,203 to $61,323) compared with controlled ($14,420 to $45,593) bleeding ( P <0.001). 17 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 20 Although there are several products available, their efficacy in controlling bleeding can be limited, with uncontrolled bleeding remaining a prevalent problem. 17 , 21 Recent data have highlighted this issue by demonstrating that 32% to 68% of surgical cases involve major bleeding, despite the use of current hemostatic agents. 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation